Pengaruh Resiliensi terhadap Peningkatan Kualitas Hidup Orang dengan TB-HIV - Indawati, Eli; Sitohang, Lestari; Hartini, Sri; Syaripudin, Yayan (Universitas Malahayati, 2025)
ABSTRACT HIV and tuberculosis are still major public health problems in Indonesia and around the world, and must beeradicated by 2030. When a person is diagnosed with HIV/AIDS, they may experience a variety of emotions, includingfear, regret, denial, confusion, and uncertainty about what to do that can lead to psychological stress. Resilience canplay a role in the quality of protection, reducing the negative impact of bad conditions that can reduce a person'squality of life. So it is necessary to increase resilience to improve the quality of life. Able to identify the effect ofresilience on improving the quality of life of people with TB-HIV. The method used in this study is